The mediating role of distress tolerance in the relationship between childhood maltreatment and anxiety in a sample of Lebanese adults - Elie Mattar; Toni Sawma; Rabih Hallit; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Souheil Hallit; Feten Fekih-Romdhane; Sahar Obeid (Scientific Reports)
Abstract Childhood maltreatment is a widespread issue worldwide and has a significant impact on the society at multiple levels, as it affects children. Numerous studies have shown the relationship between various forms of child abuse and the development of adverse outcomes in affected individuals. This study aims to assess the mediating role of distress tolerance in the relationship between childhood maltreatment and anxiety among a sample of Lebanese adults. This cross-sectional study was conducted between March and April 2024; 507 participants were recruited using a snowball sampling method. The results of the mediation analysis were adjusted over sex and physical activity. Distress tolerance partially mediated the association between child abuse and anxiety (indirect effect: Beta = 0.01; Boot SE = 0.01; Boot CI 0.001; 0.02). Higher child abuse was significantly associated with less distress tolerance and directly associated with more anxiety. Higher distress tolerance was significantly associated with less anxiety. The mediating role of distress tolerance in the relationship between childhood maltreatment and anxiety as a mental health outcome was established in this study. Thus, this study highlights the importance of enhancing distress tolerance through therapeutic means including Cognitive and Behavioral Therapies and Dialectical Behavioral Therapy. By doing so, individuals can learn to cope with anxiety caused by childhood maltreatment.